Analisis Peak Ground Acceleration Kabupaten Bantul Menggunakan Metode Campbell dan Oliviera (Studi Kasus Gempa Bumi Bantul 30 Juni 2023) - Melda Gian Priyanita; Darsono, Darsono; Handayani, Wuri (Jurnal Stasiun Geofisika Sleman, 2024)
The earthquake on June 30, 2023, centered in the southwest sea of Bantul The earthquake that occurred on June 30, 2023, with its epicenter located southwest of Bantul Regency, was one of the destructive earthquakes in Yogyakarta. One of the objectives of this study is to determine the most suitable empirical formula method for Bantul Regency in calculating the Peak Ground Acceleration (PGA) in the form of distribution maps and bar charts. The PGA value provides an indication of the level of building damage caused by the earthquake. This study conducted the PGA calculations using Campbell and Oliveira's empirical formula methods. Earthquake data were obtained from Shakemap released by BMKG. Based on the analysis, the Campbell method yielded PGA values with an MMI scale ranging from II to IV, while the Oliveira method resulted in an MMI scale ranging from II to III. The villages in Bantul Regency with the highest PGA values for each method are Parangtritis, Tirtohargo, Gadingsari, Gadingharjo, Srigading, and Poncosari.